Servant Leadership and Workplace Well-Being: Influences on Employee Engagement - Aulia, Muhammad; Roni, Shofyan; Lubis, Kartika Sari (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2025)
Purpose – This study aims to examine the influence of servant leadership and workplace well-being on employee engagement. Methodology/approach – This study applies quantitative methodology, gathering data from 614 employees by questionnaires. Withdrawing the quantity of samples that were used in the Slovin sampling technique with a critical value set at 10%. Therefore, 86 employees made up the sample for this investigation. SPSS version 25 is used for data processing. Findings – The findings obtained from this study show that: (1) Servant Leadership has a partial and significant impact on Employee Engagement, (2) Workplace Well-Being has a partial and significant impact on Employee Engagement, (3) Servant Leadership and Workplace Well-Being simultaneously have a significant impact on Employee Engagement. The adjusted R-squared value of 0.861 can be referred to as the coefficient of determination, indicating that 86.1% of Employee Engagement can be explained through Servant Leadership and Workplace Well-Being, while the remaining 13.9% is explained by external variables not examined in the model. Novelty/value – This study contributes to the human resource management literature by simultaneously examining the influence of servant leadership and workplace well-being on employee engagement in the formal sector in Indonesia. This study fills a gap in previous research, this study fills a gap by jointly analyzing servant leadership and workplace well-being, highlighting their combined role in enhancing employee engagement.